Tinjauan Kelengkapan Penulisan Nama Pasien Dalam Rekam Medis Di Rumah Sakit (Literature Review) - Anissa Yuliyanti (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: According to the Regulation of the Minister of Health of the Republic of Indonesia Number 24 of 2022 concerning Medical Records, they are documents that contain patient identity data, examinations, treatment, procedures and other services that have been provided to patients. Hospital Minimum Service Standards Completeness of medical record filling 24 hours after completion must reach 100%. Objective: To determine the completeness factor in writing the patient's name in the patient's medical record at the hospital. Method: This research used the literature review method which was carried out on 14 journals and found incompleteness in writing patient names in hospital medical records. Results: Of the 14 journals regarding the completeness of writing patient names, none of the research results found were close to the very good category (100%). The highest percentage of completeness in writing patient names was found in research journals with a percentage of 98%, while the lowest percentage was 56%. Conclusion: From the results of a review of the completeness of writing patient names in hospital medical records, 14 journals were found to not have 100% completeness results and not all hospitals have SOPs regarding procedures for writing patient names. Suggestion: Create an SPO for procedures for writing patient names that comply with standards so that officers can carry out these activities with guidelines.